8.3k views
0 votes
Q(x) = x³ − 3x² + 6x – 2
Q(0)=
Q(1)=
Q(-2)=

1 Answer

2 votes

Answer:

Q(0) = -2

Q(1) = 2

Q(-2) = -34

Explanation:

Step 1: Define

Q(x) = x³ - 3x² + 6x - 2

Q(0) is x = 0

Q(1) is x = 1

Q(-2) is x = -2

Step 2: Substitute and Evaluate

Q(0) = 0³ - 3(0)² + 6(0) - 2

Q(0) = 0 - 0 + 0 - 2

Q(0) = -2

Q(1) = 1³ - 3(1)² + 6(1) - 2

Q(1) = 1 - 3 + 6 - 2

Q(1) = -2 + 6 - 2

Q(1) = -4 + 6

Q(1) = 2

Q(-2) = (-2)³ - 3(-2)² + 6(-2) - 2

Q(-2) = -8 - 3(4) - 12 - 2

Q(-2) = -8 - 12 - 14

Q(-2) = -20 - 14

Q(-2) = -34

User Legalize
by
5.9k points